Healthy seas - "Inskipp, Carol" (Sterling Publishers New Delhi, 2006)
"Healthy Seas: Sustainable Futures," published by Sterling Publishers book is available in both hardcover and paperback editions. It focuses on topics related to marine health and sustainable practices.